Reckoning with the Legacy of Land-Grant University Libraries, Archives, and Special Collections as Ventures of Pioneer Veneration - Kersting-Lark, Dulce; Kenyon, Jylisa; Seiferle-Valencia, Marco (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2024)
Land-grant colleges and universities in the United States, and by extension their libraries and archives, seek to uphold a three-part mission of teaching, research, and service, while also focusing on equality of access, regardless of class. The admirability of that mission, however, is tempered by “genesis amnesia,” where, as Pierre Bourdieu and Jean-Claude Passeron say, “societies cover up or erase the origins of policies or institutions in order to obfuscate the social constructions that underlie them.” Other former settler colonies, such as Canada, maintain similarly structured and afflicted colleges and universities. For many institutions, the terms “land-grant,” or in Canadian contexts “land-endowed” or “land-financed,” act as a veneer, covering up and at times venerating an extractive and traumatic process by which Indigenous peoples were dispossessed of their lands. In this reflective case study, we define pioneer veneration as a symptom of colonialism and describe recent efforts to challenge it within our own library and archives. Using two collections containing Indigenous knowledges but not (primarily) Indigenous belongings, we explore our attempts to challenge pioneer veneration and seek out more impactful and purposefully reparative avenues of service to Indigenous patrons and stakeholders. By specifically defining the term pioneer veneration and discussing our institution’s effort to counter it in two specific collections, we hope to expand the lens of the types of collections that can be part of decolonization work and offer some replicable examples of work that redresses white supremacy and colonialism in institutional archives.